Atheroembolic Kidney Disease and Atypical Hemolytic Uremic Syndrome: Two Sides of the Same Coin? - Antonio Pisani; Pasquale Buonanno; Maria Amicone; Eleonora Riccio; Ivana Capuano (Kidney & Blood Pressure Research)
Introduction: Atheroembolic kidney disease (AEKD) is an under-recognized cause of kidney failure, secondary to the obstruction of the renal artery and/or its branches due to the rupture of an unstable atherosclerotic plaque in patients treated with surgical and invasive cardiovascular procedures. The embolization of cholesterol crystals in the renal artery activates the complement and triggers an inflammatory reaction. Atypical hemolytic uremic syndrome (aHUS) is a thrombotic microangiopathy caused by the hyperactivation of the alternative complement pathway, leading to a prothrombotic and proinflammatory state on the endothelial surface. AEKD and aHUS could share the involvement of the complement in their pathophysiological mechanism and the former could lead to the latter. Case Presentation: A 72-year-old man was referred to our clinic because of a rapid worsening of renal function after 9 months from an endovascular aortic repair (EVAR). After 4 months from the intervention, his renal function worsened, he developed hypereosinophilia and skin lesions; the renal ultrasound showed increased resistance indexes, strongly suggestive of atheroembolic kidney disease. Successively, we observed thrombocytopenia, anemia, increased LDH, low plasmatic haptoglobin, schistocytes in blood smear, and normal ADAMTS13. We promptly diagnosed an atypical hemolytic uremic syndrome and started ravulizumab. Conclusion: To our knowledge, this is the first case of aHUS secondary to a subacute AEKD. Further studies are necessary to fill the gap in the knowledge of the precise mechanism leading to aHUS secondary to AEKD and to confirm that they are two sides of the same coin.